2023
DOI: 10.1007/s10811-023-03061-5
|View full text |Cite
|
Sign up to set email alerts
|

A new nursery approach enhances at-sea performance in the kelp Lessonia corrugata

Allyson E. Nardelli,
Wouter Visch,
Glenn Farrington
et al.

Abstract: We found that an innovative nursery approach, where Lessonia corrugata seeded spools were cultivated by spinning to increase the water motion relative to non-spinning spools, had higher growth in both the nursery and at-sea stages. Using this method, we compared the at-sea growth of sporophytes cultivated on spinning spools at different depths (1 m, 3 m, 5 m) and seasons (timing of out-planting). Finally, we compared the at-sea growth of sporophytes cultivated on spinning spools vs. non-spinning sporophytes at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 76 publications
1
2
0
Order By: Relevance
“…In addition, higher water motion allows for denser natural beds, as the back‐and‐forth movement of the waves can in part compensate for a canopy shading effect and expose the kelps to light (Hurd, Harrison, et al., 2014; Vásquez, 1991; Vásquez et al., 2006). Our study observed a higher density of heavier kelps at Coal Point, where wave exposure was highest, consistent with previous studies on kelp species (Gerard, 1982; Nardelli et al., 2023a; Segovia et al., 2015; Vásquez, 1991; Vásquez et al., 2006). For Lessonia trabeculata in Peru, biomass per m 2 at the more exposed site was nearly double that of the sheltered site, with values of 15.2 kg wet weight · m −2 and 8.3 kg wet weight · m −2 , respectively (Aller‐Rojas et al., 2020).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, higher water motion allows for denser natural beds, as the back‐and‐forth movement of the waves can in part compensate for a canopy shading effect and expose the kelps to light (Hurd, Harrison, et al., 2014; Vásquez, 1991; Vásquez et al., 2006). Our study observed a higher density of heavier kelps at Coal Point, where wave exposure was highest, consistent with previous studies on kelp species (Gerard, 1982; Nardelli et al., 2023a; Segovia et al., 2015; Vásquez, 1991; Vásquez et al., 2006). For Lessonia trabeculata in Peru, biomass per m 2 at the more exposed site was nearly double that of the sheltered site, with values of 15.2 kg wet weight · m −2 and 8.3 kg wet weight · m −2 , respectively (Aller‐Rojas et al., 2020).…”
Section: Discussionsupporting
confidence: 92%
“…This fraction of the global NPP occurs in an area that is <2% of the global ocean surface, which makes this environment highly productive (Duarte, 2017). Kelp forests are particularly productive in temperate regions and areas with permanent upwelling (Krumhansl & Scheibling, 2012; Nardelli, Visch, Farrington, et al., 2023; Yoneshigue & de Oliveira, 1987). This high productivity supports complex ecosystems that rely on these kelps both for food and habitat provision (Bularz et al., 2022; McLachlan, 1985; Pérez‐Matus et al., 2017) and for delivering other crucial ecosystem services, such as carbon storage and cycling (Bennett et al., 2015; Filbee‐Dexter & Wernberg, 2020; Gao et al., 2021; Ramus, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation